2012
DOI: 10.1002/hbm.22055
|View full text |Cite
|
Sign up to set email alerts
|

The structural correlates of functional deficits in early huntington's disease

Abstract: Neuropathological studies in Huntington disease (HD) have demonstrated neuronal loss in the striatum, as well as in other brain regions including the cortex. With diffusion tensor MRI we evaluated the hypothesis that the clinical dysfunction in HD is related to regionally specific lesions of circuit-specific cortico-basal ganglia networks rather than to the striatum only. We included 27 HD and 24 controls from the TRACK-HD Paris cohort. The following assessments were used: self-paced tapping tasks, trail B mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 78 publications
3
63
0
2
Order By: Relevance
“…Abnormal eating behaviours are a cardinal feature of behavioural variant frontotemporal dementia (bvFTD) [13][14][15][16][17][18][19] : such abnormalities could be at least partly underpinned by deficits of flavour processing, and have been linked to cortical atrophy in a distributed network including the orbitofrontal cortex (OFC), anterior insula and striatum. [13][14][15][16][17][18][19] Overlapping grey matter correlates have been identified for odour identification performance in neurodegenerative diseases, [20][21][22] and these correlates align with the distributed frontotemporal-subcortical network implicated in flavour processing in functional imaging studies of the healthy brain. [2][3][4][5][6] Previous group analyses of patients with FTLD have examined processing of elementary taste qualities and recognition of the multimodal stimuli embodied in natural foods.…”
Section: Introductionmentioning
confidence: 89%
“…Abnormal eating behaviours are a cardinal feature of behavioural variant frontotemporal dementia (bvFTD) [13][14][15][16][17][18][19] : such abnormalities could be at least partly underpinned by deficits of flavour processing, and have been linked to cortical atrophy in a distributed network including the orbitofrontal cortex (OFC), anterior insula and striatum. [13][14][15][16][17][18][19] Overlapping grey matter correlates have been identified for odour identification performance in neurodegenerative diseases, [20][21][22] and these correlates align with the distributed frontotemporal-subcortical network implicated in flavour processing in functional imaging studies of the healthy brain. [2][3][4][5][6] Previous group analyses of patients with FTLD have examined processing of elementary taste qualities and recognition of the multimodal stimuli embodied in natural foods.…”
Section: Introductionmentioning
confidence: 89%
“…Still, cortical atrophy in combination with striatal atrophy has also been linked to cognitive symptoms in HD 58. Similarly, cortico-subcortical white matter tract changes have been associated with those deficits 59. Finally, functional imaging studies of cognitive changes in HD have consistently found cortical and striatal activation alterations compared with healthy controls in relation to cognitive load, planning, attention60 and more specifically, ventral striatal regions being related to reward processes 61.…”
Section: Disorders With Well Described Striatal Dysfunctionmentioning
confidence: 99%
“…This level of accuracy was slightly higher than that (76%) found using machine learning approaches and voxel-based volumetric analysis [61]. Another study [62] found that motor and cognitive tasks were correlated with abnormal dMRI measures in multiple areas of GM and WM, suggesting that dysfunction in extra-striatal areas of the brain are related to clinical manifestations in a region-specific manner. Dumas and colleagues [53] found more widespread dMRI abnormalities in early manifesting compared to pre-manifesting HD, with correlations between dMRI and clinical measures.…”
Section: Huntington’s Diseasementioning
confidence: 76%